Combined eosinophilic gastroenteritis and ulcerative colitis successfully treated by vedolizumab: a case report - Hironobu Takedomi; Kayoko Fukuda; Suma Inoue; Nanae Tsuruoka; Yasuhisa Sakata; Shigehisa Aoki; Motohiro Esaki (Intestinal Research)
A 47-year-old man with over 10 years’ duration of ulcerative colitis treated by 5-aminosalicylic acid and intermittent topical steroids complained of acute epigastric pain. Esophagogastroduodenoscopy revealed diffuse mucosal edema with patchy redness, multiple erosions and nodularity of the stomach. Bioptic examination revealed marked eosinophilic infiltration, confirming the diagnosis of eosinophilic gastroenteritis. Systemic steroid therapy was initiated, whereas his ulcerative colitis and eosinophilia recurred when tapering the steroid. Addition of azathioprine was ineffective, and we subsequently started vedolizumab for eosinophilic gastroenteritis and ulcerative colitis. The medication effectively improved his abdominal symptoms and esophagogastroduodenoscopy and ileocolonoscopy 1 year later revealed endoscopic improvement of both diseases with histologically decreased level of eosinophilic infiltration. Considering that eosinophils also express α4β7 integrins, vedolizumab can be a possible therapeutic candidate for eosinophilic gastroenteritis as well as ulcerative colitis.